AGRIS: increasing its activity in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The International Information System for the Agricultural Sciences and Technology (AGRIS) is one of the world's largest agricultural informat~on systems and the only one which has tried to give equal emphasis to the needs of developing and developed...